2012
DOI: 10.1055/s-0032-1312877
|View full text |Cite
|
Sign up to set email alerts
|

Average Glandular Dose in Digital Mammography and Breast Tomosynthesis

Abstract: In this study the mean calculated AGD per exposure in 3 D imaging mode was on average 34% higher than for 2 D imaging mode for patients examined with the same CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
36
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 12 publications
8
36
2
5
Order By: Relevance
“…It was evident that AGD from DBT was lower than that for FFDM. Which is similar to the study of Svahn TM etal but controversial to the study of Olgar T etal [3] . Further AGD was reduced by 55.3% by using DBT with compared to TAGD, using both FFDM and DBT together for same patient and AGD was reduced 19.19% by using DBT with compared to AGD from FFDM.…”
Section: Discussion:-supporting
confidence: 77%
“…It was evident that AGD from DBT was lower than that for FFDM. Which is similar to the study of Svahn TM etal but controversial to the study of Olgar T etal [3] . Further AGD was reduced by 55.3% by using DBT with compared to TAGD, using both FFDM and DBT together for same patient and AGD was reduced 19.19% by using DBT with compared to AGD from FFDM.…”
Section: Discussion:-supporting
confidence: 77%
“…For screening, the additional radiation associated with tomosynthesis (equivalent to 1.4 mammography films) [51] should also be considered. A dosimetric study carried out on our machine showed that the dose of one tomosynthesis incidence was identical to one standard mammography film [52].…”
Section: Discussionmentioning
confidence: 99%
“…Included in the research database were deidentified mammography and tomosynthesis images, imaging reports, and surgical pathology results if an image-guided biopsy and/or surgery was performed. Inclusion criteria for this study were (a) the availability of the tomosynthesis in combination with FFDM increases radiation dose above that of FFDM alone, roughly by a factor of two (21,22). Despite the improvements in accuracy found to date by using combined tomosynthesis and FFDM, the increased radiation dose to the patient is of concern.…”
Section: Case Selectionmentioning
confidence: 99%